Edema, Ecchymosis, and Pain: Classic versus Electric Micro-Saw Osteotomy - Bayrakci, Erdem; Aricigil, Mitat; Eryilmaz, M. Akif; Eravci, Fakih Cihat; Arbağ, Hamdi (Facial Plastic Surgery, 2025)
To compare postoperative edema, ecchymosis, and pain after rhinoplasty using conventional (classical) osteotomy versus powered (electric) micro-saw osteotomy techniques. Between December 2021 and May 2023, 90 patients aged 18 to 45 underwent rhinoplasty at our clinic. Of these, 45 patients underwent lateral and transverse osteotomy with powered saw instruments, whereas 45 underwent conventional osteotomy. A resident examined edema, ecchymosis, and pain on the first, third, and seventh postoperative days. The specialist was blinded to the osteotomy method (single-blind). Edema and ecchymosis were categorized using the Yücel modification of the Kara and Gokalan classification, and the pain was evaluated using the visual analog scale. The patients who underwent osteotomy with an electric micro-saw (group 1) had less edema on the first and third days than with conventional osteotomy (group 2). However, on the seventh day, although group 1 had slightly less edema than group 2, there were no significant differences. On the other hand, group 2 had significantly more ecchymosis on the first and third postoperative days compared with group 1, but there were no significant differences on the seventh day. On the first postoperative days, patients in group 2 reported significantly more pain on average compared with group 1. There were no significant differences in pain levels between the two groups on the third and seventh days following the surgery. After rhinoplasty, patients commonly suffer from edema, ecchymosis, and pain. Our research suggests that using a powered micro-saw effectively reduces early-stage ecchymosis and pain compared with the conventional low-to-low osteotomy technique. However, there were no notable differences between the two methods regarding edema, ecchymosis, and pain on the seventh day after surgery. The electric micro-saw appears to be a feasible alternative in the osteotomy step, showing effectiveness comparable to that of the conventional method.
Keywords: rhinoplasty; osteotomy; micro-saw; edema; ecchymosis